Материалы по акклиматизации горбуши в бассейне Балтийского моря. - Rimsh, E.Ya.; Ivanova, G.T. (1978)
The experimental works on pink salmon acclimatization began in 1972. Yearly pink salmon egg at "eye" stage was being brought from Sakhalin hatcheries and put into Atkins type hatching apparatus, installed at salmon hatcheries of the Latvian SSR for final incubation. The duration of final incubation stage of egg made up 35-45 days. The mass hatch of pink salmon pro-larvae was observed in observed in the middle of December. The resting stage of pro-larvae lasted 3—4 months: at hatcheries with a spring source of water supply it formed 86-95 days, at the hatcheries with a river source of water-supply 109-122 days. On the whole the first stages of pink salmon life (embryonic and postembryonic periods of development) were quite successful. Pink salmon fry was released into Latvian rivers with a batch from 170 to 420 mg. The dates of release were different. The best results were obtained, when pink salmon fingerling release was carried out at the end of April. The growth rate of pink salmon in the sea period of life is high. Pink salmon length-weight data in a new and natural areal are similar. Pink salmon survival in the sea period of life is low. The coefficient of the return (registered) fluctuated from 0,005 to 0,4 % in the time of researches from 1974 to 1976. 3. ausgabe des sonderheftes über fischereiliche untersuchungen der DDR und der UDSSR in der Ostsee. 3. выпуск совместного сборника научных статей по вопросам рыбохозяйственных исследований ГДР и СССР в Балтийском море. Published